Examination of the human remains from the medieval cemetery of Bátmonostor-Pusztafalu in Hungary - Farkas, Gyula L.; Józsa, László; Bereczki, Zsolt (Acta Biologica Szegediensis, 2007)
This paper summarizes the results of the physical anthropological examinations carried out on the remains of 3783 individuals from the medieval cemetery of Bátmonostor- Pusztafalu in Hungary. Distributions of sex and age at death are described along with the observations made concerning anatomical variations, developmental anomalies, pathological alterations and taxonomic features. This study is the shorter version of a more detailed paper to be published in Opuscula Hungáriáé.